Vibration Localization in Cyclic Mistuned Structure and Its Application to Low-Frequency Broadband Vibration Control of Pipelines - Lihang Yin; Wei Xu; Jian Zhou; Song Liu; Liantao Xiao (Applied Sciences)
This paper proposes a pipeline vibration control method based on the vibration localization energy dissipation principle of cyclic mistuned structure (CMS). The influence of the frequency mistuning strength and coupling strength of the resonant units on vibration localization characteristics is studied using perturbation analysis. Subsequently, numerical simulations are conducted to verify the theoretical results. Theoretical and numerical results indicate that setting an appropriate mistuning strength and minimizing the coupling strength are conducive to achieving broadband vibration reduction. On this basis, a pipeline-oriented CMS is proposed. It achieves low-frequency broadband vibration control of pipelines by regulating the frequency mistuning strength of the resonant units located in the annular hierarchical honeycomb structure. Finally, tests are conducted to verify the vibration reduction performance of the CMS. Following the installation of the CMS, the frequency response function (FRF) amplitude of the pipeline steadily decreases over a wide frequency band. The excitation test results indicate that the CMS reduced the acceleration amplitude of the pipeline by 34.7 dB at 82.5 Hz, 16.0 dB at 90 Hz, and 19.8 dB in the broadband vibration level between 70 Hz and 120 Hz.